Association between infant nutrition and later body composition - Kagura, Julia (My University, 2011)
Background: The long term effect of infant nutrition on later body composition has gained global attention since the developmental origins of health and disease because of the association between early life outcomes and later adult health (1). Under-nutrition and growth faltering during prenatal and infant periods have been reported to be related to subsequent growth faltering, high fat mass, and low lean and bone mass. Early life nutritional environmental cues may cause permanent effects on the physiology, metabolic and endocrine system of the body. Objective: We investigated the association of infant nutrition and anthropometry with subsequent child anthropometry and body composition at age 9/10 years. Design: This study comprised of 140 children who had infant growth measures and dual-energy X-ray absorptiometry (DXA) conducted at age 9/10 years. They were selected from the Bone health sub-study of 408 black children of the Birth-Twenty longitudinal study cohort comprising of children born in Soweto, Johannesburg in 1990. Data collection and analysis: Data was collected on following variables; infant feeding, socio-economic status at delivery, anthropometry (birth weight, height and weight at ages 1, 2, 9/10 years). Body composition data was obtained from DXA scans. Food frequencies questionnaires were used for dietary patterns data collection. Data cleaning and analysis of data which encompassed descriptive, bivariate and multivariate analyses were done in STATA 10 and the 5% level of significance was used for statistical significance. Results: Children were breast-fed on average for 13 months in boys and 16 months in girls (p=0.009) while those bottle fed had a duration of 10 months for both sexes. Introduction of solid foods was around 3 months while the approximate mean dietary diversity score (the number of food groups consumed by an infant in a 24-hour recall period) was 1 and the food iv variety score (the number of food items consumed by an infant in a 24-hour recall period) was 2 for both girls and boys. Prevalence of stunting, wasting and underweight at 1 year was 8.6%, 3.6% and 8.6% respectively. At age 2 years, the prevalence was 15.7%, 8.6% and 16.4% for stunting, wasting and underweight, respectively. All the associations between infant nutrition variables and subsequent growth and body composition at age 9/10 years were statistically non-significant. In the multivariate model, increase in birth weight predicted an increase in weight and height at ages 1, 2 and 9/10 years, lean mass (β=0.20, CI=0.01-0.03, p=0.007), radius (β=0.02, CI=0.00-0.04, p=0.039) and lumbar spine (β=0.03, CI=0.01-0.05, p=0.018). Infant weight and height at 1 year were significantly positively associated with subsequent growth at 2 and 9/10 years and with body composition variables. Stunting at age 1 year was significantly associated with lower fat mass (β= -0.18, CI= -0.03 to -0.06, p=0.003) while stunting at age 2 years predicted lower fat only (β= -0.12, CI= -0.22 to -0.03, p=0.011) after adjusting for confounders. Being underweight at age 2 years predicted lower fat mass in the multivariate model. Conclusion: Infant nutrition had no significant influence on subsequent growth and body composition. Birth weight and infant anthropometry; particularly height, weight, stunting and underweight are the main predictors of body composition at age 9/10 years. There is need for promotion of optimal prenatal and infant growth in children to reduce risk of chronic diseases like Type 2 diabetes, hypertension and osteoporosis in later life.
MSc (Med), Child Health, Faculty of Health Sciences, University of the Witwatersrand, 2011
Keywords: infant nutrition; child nutrition; physical development